The comparison of emotional intelligence between team and individual sports female players - kaur, Jagjiwan; Gahlawat, Ravi Kumar; Singh, Sukhwinder (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The objective of present paper is to find the emotional intelligence differences between team and individual sports female players. Purposive sampling technique is used to select the 300 female players from team sports (150) and individual sports (150).  The age of subjects is ranging between 18 to 25 years. Further, the study is delimited to all India inter- university and national level players of Punjab. Players of hockey, Volleyball, Basketball, Football and handball served as subjects for team sports and players from wrestling, judo, boxing, fencing, weight lifting served as subjects for individual sports. Emotional intelligence questionnaire comprising 34 items by Hyde et al. (2001) was used as data collection tool. To examine the significance differences between groups unpaired t-test is used to test hypothesis at level of 0.05. The results (t = 1.5491, P >0.05) Indicated that there is no significant difference between team sports (132.43 ± 9.85) and individual sports (130.9 ± 6.97). The difference (1.53) between means is in favour of team sports. So, it can be concluded that analysis for various sub-parameters (self-awareness, empathy, self-motivation, emotional stability, managing relations, integrity, self- development, value orientation, commitment & altruistic behaviour) of emotional intelligence between team and individual sports may reveal some guiding facts for coaches and physical educationists.